DNA Methylation Patterns of Interferon Gamma Gene Promoter and Serum Level in Pulmonary Tuberculosis: Their Role in Prognosis (Baghdad Science Journal, 2019)
Tuberculosis (TB) still remains an important medical problem due to high levels of morbidity and mortality worldwide. A series of innate immune mechanisms that create a cytokine network control the pathogenesis of tuberculosis and this response has the capacity to modify the host genomic DNA structure through epigenetic mechanisms such as DNA methylation which could constantly alter the local gene expression pattern that can modulate the metabolism of the tissues and the immune-response. Interferon-gamma (IFN-γ) is an important pro-inflammatory cytokine regulator of the innate immune response to TB. This study aims to determine DNA methylation patterns of INF-γ gene promoter and measure serum IFN- γ level in newly diagnosed TB patients, relapse TB patients, and healthy control, in order to study the possibility of using these as a biomarker for the prognosis of TB stages in patients. The current case-control study included 66 patients with TB and 33 healthy control subjects. DNA was extracted from peripheral blood(PB) of included subjects and modified using sodium bisulfate specific kit. DNA methylation patterns of IFN-γ gene promoter was determine by using methylation specific polymerase chain reaction(MS-PCR).Serum IFN-γ level was determined using enzyme linked immune-sorbent assay(ELISA). Results showed that percentages of DNA methylation patterns in normal controls, newly diagnostic TB patients and relapse TB patients were (63.3%, 18.2% and 21.2% respectively). Also, higher significant differences (P≤0.0001) of un-methylated IFN-γ gene promoter patterns in newly diagnostic TB patients than relapse TB patients comparison with healthy controls. The percentage of un-methylated DNA patterns in healthy controls, newly diagnostic TB patients and relapse TB patients were (9.9%, 39.4% and 51.5%, respectively). The mean of serum IFN-γ levels (pg/ml) for normal controls, newly diagnostic TB patients and relapse TB patients were (59.3± 13.8,75.8±24.3 and 69.6±18.7,respectively).In conclusion, there is a relative association between methylation of IFN-γ gene promoter and predisposing to TB progression.